The role of glial cells in neuralgia: a bibliometric exploration - He, Ting; Wang, DongDong; Wu, Linman; Jin, Liuyin (Frontiers in Neurology, 2025)
Neuropathic pain is a chronic pathological pain caused by nervous system damage, characterized by complex mechanisms and limited treatment efficacy. Glial cells play a pivotal role in the initiation and maintenance of neuropathic pain. This study employs bibliometric analysis to explore trends and emerging hotspots in research on the relationship between glial cells and neuropathic pain. Based on literature data from the Web of Science Core Collection spanning 2003 to 2022, the study identifies key contributors in the field, including leading countries such as China, the United States, and Japan, as well as influential institutions and journals, such as the University of California system and Pain. Keyword analysis highlights research hotspots focusing on glial cell activation, spinal cord injury, satellite glial cells, oxidative stress, and neuroinflammation. The findings suggest that these themes may shape future directions in the field. This study provides researchers with a comprehensive overview of trends and hotspot analysis, offering valuable insights for further investigation into the role of glial cells in neuropathic pain.